Differential Cytokine Expression in Natural and Experimental Mastitis Induced by Mycoplasma agalactiae in Dairy Goats. Issue 1 (15th November 2014) - Rodríguez, F; Castro, P
Contents Cytokines, primarily produced by macrophages and lymphocytes, mobilize the immune system in response to infection, particularly at mucosal surfaces. Knowledge of the pathogenesis and persistence of Mycoplasma agalactiae (Ma) in the mammary gland is still insufficient. The aim of this study was to elucidate the role of cytokines in the pathogenesis of caprine mastitis caused by Ma. Cytokine expression was evaluated by immunohistochemical methods in the inflammatory lesions of 10 (5 naturally and 5 experimentally infected) goats with Ma‐induced mastitis. Immunolabelling for IL‐10, IFN‐γ, IL‐4 and TNF‐α was observed in inflammatory cells within the lumen of acini and ducts and in the interstitial spaces and was usually associated with the presence of Ma antigen. The results suggest that cytokines play a role in the pathophysiological processes during Ma infection as differential expression of these cytokines was detected in relation to the course of the infection.